162 Tobacco Smoking and Outcomes of Surgical Decompression in Patients With Symptomatic Degenerative Cervical Spondylotic Myelopathy. (August 2016) - Arnold, Paul M.; Kopjar, Branko; Tetreault, Lindsay; Nakashima, Hiroaki; Fehlings, Michael G.
Abstract : INTRODUCTION: Tobacco smoking has been associated with poor outcomes following surgery for cervical radiculopathy. However, the impact of tobacco smoking on outcomes following surgery for degenerative cervical spondylotic myelopathy (DCSM) has not been extensively evaluated. METHODS: This study analyzed prospectively collected data from 2 large multicenter international cohort studies. Outcome measures were preoperative smoking status, modified Japanese Orthopedic Association scale (mJOA), Nurick score, Neck Disability Index (NDI), Short Form 36v2 (SF-36v2"!), and the 30-m walk test (30MWT). Analysis of covariance was used to evaluate differences in outcomes at 12 months between smokers and nonsmokers while controlling for relevant baseline characteristics. RESULTS: Seven hundred forty-nine patients with symptomatic DCSM underwent surgical decompression at 24 international sites. There were 547 (73%) nonsmokers and 202 (27%) smokers. After imputation of missing 12-month scores, 694 (92.66%) subjects had 12-month data. Smokers were younger (average 53.40 vs 57.42 years) and had worse preoperative NDI, SF-36v2 Physical Component Score (PCS) and SF-36v2 Mental Component Score (MCS) ( P < .1). There were no differences in sex, race, symptom duration, etiology, number of operated levels, disease severity, or complication or reoperation rates. At 12 months, improvements in mJOA, NDI, and SF-36v2 PCS outcomes were 15.59%, 31.61%, and 28.57% lower in smokers than in nonsmokers. Following adjustment for confounders, these differences remained significant. CONCLUSION: Preoperative tobacco smoking is strongly associated with suboptimal clinical, functional, and quality-of-life outcomes in patients undergoing surgery for DCSM. Although both nonsmokers and smokers benefited from surgical decompression, the extent of improvement was higher in nonsmokers than smokers.